One physicist's guide to nuclear weapons : a global perspective - Bernstein, Jeremy, 1929- (IOP (Series). Release 3., 2016)
One Physicist's Guide to Nuclear Weapons presents a truly global look at the history, use, and issues surrounding nuclear weapons from the perspective of physicist and writer Jeremy Bernstein. A first-hand witness to the development and science of nuclear weapons, he is in a unique position to highlight the ways in which nuclear weapons work with a writing style that is suitable for lay readers and scientists alike. Bernstein brings the reader on a journey from the Nevada nuclear-testing fields in the 1950s to the present day situations in Iran and North Korea, while delving into the physics and science behind the bomb. With an introduction by Sir Chris Llewellyn Smith, this book is a testament to the last 70 years of the nuclear age, affecting every human being on the planet.